Amidophosphine‐stabilized palladium complexes catalyse Suzuki–Miyaura cross‐couplings in aqueous media. (30th June 2016) - Jansa, Josef; Řezníček, Tomáš; Dostál, Libor; Růžičková, Zdena; Bureš, Filip; Jambor, Roman
Abstract : We report a simple and efficient procedure forSuzuki–Miyaura reactions in aqueous media catalysed by amidophosphine‐stabilized palladium complexes trans ‐L 3 PPh2 2 PdCl2 (3 ), trans ‐L 3 PPh t Bu2 PdCl2 (4 ), [Pd(η 3 ‐C3 H5 )(L 3 PPh2 )Cl] (5 ) and Pd[2‐(Me2 NCH2 )C6 H4 ](L 3 PPh2 )Cl (6 ). The acidity of the NH proton in complexes3, 4, 5, 6 plays an important role in theircatalytic activity . In addition, the palladium complexes cis ‐L 1 PPh2 PdCl2 (1 ) and trans ‐L 2 PPh2 2 PdCl2 (2 ) stabilized by phosphines containing Y, C, Y‐chelating ligands L 1, 2 have also been found to be useful catalysts forSuzuki–Miyaura reactions in aqueous media. The method can be effectively applied to both activated and deactivated aryl bromides yielding high or moderate conversions. Thecatalytic activity of couplings performed in pure water increases when utilizing a Pd complex with more acidic NH protons. A decrease of palladium concentration from 1.0 to 0.5 mol% does not lead to a substantial loss of conversion. In addition, Pd complex1 can be efficiently recovered using two‐phase system extraction. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A simple and efficient procedure is reported for Suzuki reaction in aqueous media catalysed by stabilized palladium complexes1–6 . The acidity of the NH proton in3–6 plays a role in catalytic activity and that in pure water increases when utilizing Pd complex with more acidic NH protons. The concentration of palladium catalysts can be reduced to 0.5 mol% without substantial loss of conversion. The possible recovery of1 from water was also investigated.